Inflammation and Epithelial-Mesenchymal Transition in Pancreatic Ductal Adenocarcinoma: Fighting Against Multiple Opponents. (12th May 2017) - Khalafalla, Farid G; Khan, Mohammad W
Pancreatic ductal adenocarcinoma (PDAC) is the most common type of pancreatic cancer and one of the most lethal human cancers. Inflammation is a critical component in PDAC initiation and progression. Inflammation also contributes to the aggressiveness of PDAC indirectly via induction of epithelial-mesenchymal transition (EMT), altogether leading to enhanced resistance to chemotherapy and poor survival rates. This review gives an overview of the key pro-inflammatory signaling pathways involved in PDAC pathogenesis and discusses the role of inflammation in induction of EMT and development of chemoresistance in patients with PDAC.